1999
DOI: 10.1002/(sici)1099-1018(199911/12)23:6<297::aid-fam702>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Occupants' behaviour in response to the high-rise apartments fire in Hiroshima City

Abstract: A remarkable, large fire occurred in a 20 stories high‐rise apartments in 1996 in Hiroshima City. The fire spread from the fire origin apartment unit on the 9th floor up to the top 20th floor, very quickly by external flame spread through balconies. The authors investigated the evacuation behaviour of the occupants including reaction to fire cues, motives for starting evacuation, and choice of evacuation route by means of questionnaire survey and also peer interviews with some of them, focusing on the use of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(24 citation statements)
references
References 0 publications
0
24
0
Order By: Relevance
“…In countries such as the UK, Australia, Malaysia, China and USA, lifts are either being used or being considered for use as part of building evacuation systems. In past ad-hoc egress situations lifts have been used to good effect to assist in the rapid evacuation of highrise buildings [1]. In such cases lifts were not intended to form part of the evacuation system but were used by residents for rapid egress.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In countries such as the UK, Australia, Malaysia, China and USA, lifts are either being used or being considered for use as part of building evacuation systems. In past ad-hoc egress situations lifts have been used to good effect to assist in the rapid evacuation of highrise buildings [1]. In such cases lifts were not intended to form part of the evacuation system but were used by residents for rapid egress.…”
Section: Introductionmentioning
confidence: 99%
“…While several studies have postulated human response to the use of lifts during evacuations [4,5], certain studies have interviewed survivors who used lifts during real evacuations/drill [1,3,6] and some studies have conducted surveys [6], there is still a lack of understanding regarding the key factors which influence human behaviour relating to lift/stair selection during evacuations. Indeed whilst past studies have provided insight into such behaviour, most have been narrow in their focus resulting in questionable general applicability, for example, focusing on narrow population age groups (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Though not related to an earthquake, the second largest damage of 580 square meters, recorded in an event in Hiroshima in October 1996, was also a multiple compartment / apartment fire in a 20-story building. The fire originated on the 9 th floor, spreading up by way of balconies, finally reaching the top of the building [9]. Table 4 gives the amount of data as well as estimated HD parameters.…”
Section: Distinctions Of Two Different Categories Of Risksmentioning
confidence: 99%
“…Recent studies have investigated the importance of an appropriate egress strategy when using evacuation elevators. Actual evacuation scenarios showed that, elevators can be used to assist the evacuation of a high-rise building (Averill, et al, 2005;Sekizawa, et al, 1999). Special requirements are also related to emergency power supply and water protection (Bukowski, 2005;Bukowski, 2010b).…”
Section: Introductionmentioning
confidence: 99%